PENGARUH EMULSIFIER TERHADAP STABILITAS EMULSI SALAD DRESSING BERBAHAN MINYAK JAGUNG - Ery Fatarina; Rudi Firyanto; Sri Mulyaningsih; Hilda Nur P (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2017)
Corn oil is a food that quite known, but it’s still not optimal. Salad Dressing is one of food product that makeby homoginezer process from oil and water. Emulsifier should be added to keep emultion system stability sothat it not easy for oil and water to be sparated. The experimental aim to find natural emulsfier effect (egg) tosalad dressing emultion satbility and find the product specification that has been made. This experimentconducted by mixing corn oil and lime juice water with a ratio of 250 ml : 25 ml with homoginezer’s duration1,2 and 3 minute, emulsifier’s volume 10,20 and 30 ml, and homoginezer’s velocity 9000, 12000 and 15000rpm. The variabels that has been looked are viscosity, density, also surface tension. The optimal result ofemulsifier volume is 28.2669 ml, homoginezer’s velocity is 9000,14 rpm and homoginezer’s duration 2.9987minute. The optimal equal to viscosities respond (Cp) = -1,20767 + 0,64850 x A + 4,38333E-4 x B +0,02250 x C, the equal respon for dencities respond (g/cm3) =+ 0.76749+7.08125E-3 x A-3.125E-6xB+6.875E-4 x C and the optimal equal to tension respond (N/m)=0.28453-5.0675E-3 xA-1.55E-6 x B+1E-4x C. The salad dressing product with specification pH 4-5, viscosity between 17.85 Nm-2s-1 - 66.76 Nm-2s-1,and surface tension between 0.0942 to 0.1954 N / m. Thus, salad dressing with basic material of Corn Oilhas a good quality.